An efficient N-to-1 multipath routing protocol in wireless sensor networks - Wenjing Lou (IEEE International Conference on Mobile Adhoc and Sensor Systems Conference, 2005, 2005)
A typical task in a wireless sensor network is that every sensor node senses its local environment and, upon request, sends the data of interest back to a base station. Based on this many-to-one communication pattern, we first propose a distributed N-to-1 multipath discovery protocol which distinguishes from other multipath routing protocols in that it is able to find multiple node-disjoint paths from every sensor node to the base station simultaneously in one route discovery process. Then we propose a hybrid multipath data collection scheme which combines end-to-end multipath traffic dispersion and per-hop alternate path salvaging. Our simulation results show that the proposed N-to-1 multipath discovery protocol is highly efficient and the hybrid data collection scheme based on it provides a seamlessly more reliable and more secure data collection service in wireless sensor networks